Pemikiran K.H. Ahmad Dahlan : Tipologi Dakwah Performatif dan Transformatif di Indonesia - Ismail Ismail; Nadia Cahaya Amanda (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Contemporary Islamic preaching (dakwah) faces increasingly complex structural pressures: digital platforms offer unprecedented reach, yet the attention economy ecosystem systematically pushes dakwah to align with the logic of viral, easily consumable, and engagement-oriented content. Consequently, a fundamental and urgent question arises: does dakwah still function as an agent of social change, or has it transformed into a component of the religious entertainment industry? This article responds to that question by constructing a typology of performative dakwah and transformative dakwah. This analytical framework distinguishes between preaching oriented toward symbolic representation and audience consumption versus preaching focused on tangible and measurable social change. A distinctive feature of this article is that this typology is not built from theoretical frameworks imported from outside the Islamic tradition, but is instead extracted from the thoughts and practices of K.H. Ahmad Dahlan, the founder of Muhammadiyah, who consistently rejected verbalistic dakwah and placed social transformation at the core of the Islamic mission. Using a qualitative approach based on library research and critical-conceptual analysis, this study demonstrates that K.H. Ahmad Dahlan’s logic centered on the unity of faith, knowledge, and action, along with an explicit bias toward marginalized groups provides a robust theological and methodological foundation for evaluating contemporary digital dakwah trends. The findings indicate that most digital dakwah in Indonesia today leans toward performative patterns, and while the space for transformative dakwah in the digital era is narrow, it remains viable and must be consciously nurtured.